The importance of nursing actions for the prevention, screening, and treatment of sexually transmitted infections in the elderly (Research, Society and Development, 2022)
Nursing actions for the prevention, tracking and treatment of various pathologies are extremely important. With regard to sexually transmitted infections (STIs) in old age, these actions are even more important for the quality of life of this growing population, both due to the availability of medication and technological developments. With this, the elderly are living longer and expanding their active sex life. In this context, this article aims to describe in the literature the importance of Nursing actions and knowledge about STIs in old age. This is a narrative literature review. For data collection, a survey was carried out between July and November 2022 in the databases: Virtual Health Library (BVS); Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Ministry of Health (Brazil) and Brazilian Institute of Geography and Statistics (IBGE). 12 documents relevant to the study were selected and two categories were created: knowledge about STIs in old age and the importance of nursing actions regarding STIs for this public. The results contribute to the discussion about the need for health professionals to pay more attention to sexuality among the elderly. Thus, it is expected that the present study will collaborate with the awareness of the importance of nursing work on STIs in the prevention, screening and treatment of STIs for the elderly public.